Information Security Protection of Distributed Energy Stations under the Environment of Energy Internet - Daogang PENG; Tao WEI; Jun YAO; Kai ZHANG; Fei XIA (Zhongguo dianli)
The construction of distributed energy stations in the energy internet introduces network information technology and standard data transmission communication protocols, which will also leads to the threats and risks of information security. Information security is an important cornerstone for ensuring the development of distributed energy stations under energy internet environment, and construction of safe distributed energy stations is an inevitable trend of energy internet development. From the perspective of information security threats faced by energy and power systems, the system architecture of distributed energy stations under energy internet environment is designed in this paper, and the information security protection measures of distributed energy stations are analyzed. A distributed energy station platform is constructed to analyze the information security protection configuration and application. The study results can provide a guideline for implementation of the information security of distributed energy stations.